Prenatal malaria exposure and risk of adverse birth outcomes: a prospective cohort study of pregnant women in the Northern Region of Ghana. Issue 8 (1st August 2022) - Hussein, Hawawu; Shamsipour, Mansour; Yunesian, Masud; Hassanvand, Mohammad Sadegh; Agordoh, Percival Delali; Seidu, Mashoud Alabi; Fotouhi, Akbar
Abstract : Objective: Malaria remains endemic in most of sub-Saharan Africa and has a negative impact among pregnant women, resulting in morbidity and poor birth outcomes. The purpose of this study was to assess the relationship between malaria and adverse birth outcomes among prenatal women in the Northern Region of Ghana. Design: This is a prospective cohort study of singleton pregnancies at 28 weeks of gestational age and above recruited between July 2018 and May 2019 from four public hospitals in the Northern Region of Ghana. Outcome measures: Low birth weight (LBW), preterm birth and perinatal death. Results: A total of 1323 pregnant women completed the study out of the 1626 recruited, with an average age of 27.3±5.2 years. The incidence of malaria in this population was 9.5% (95% CI 7.9 to 11.1). After adjusting for newborn admissions to the neonatal intensive care unit, parity, maternal age and glucose-6-phosphate dehydrogenase, women who were exposed to malaria during the third trimester of pregnancy had 2.02 times (95% CI 1.36 to 2.99) higher odds of premature delivery. Furthermore, they had 2.06 times (95% CI 1.09 to 3.93) higher chance of giving birth to babies with LBW, irrespective of their socioeconomic status. With an OR of 1.02 (95% CI 0.26 to 4.01), there was no difference in perinatal mortality between pregnant women with malaria and those without malaria after adjusting for caesarean section. Conclusion: This study confirms that prenatal malaria increases the odds of both preterm and LBW deliveries. A decisive policy to eradicate or minimise perinatal malaria is needed to contribute to the prevention of LBW and adverse pregnancy outcomes.